QUANTITATIVE ANALYSIS OF RNA AND ACIDIC PROTEINS OF MONOBLASTS AND MONOCYTES INFECTED WITH AFRICAN SWINE FEVER VIRUS (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
A single cell cytophotometry was used to analyze the amount of RNA and proteins in porcine cells that are susceptible to African Swine Fever Virus (ASFV). The obtained results show that ASFV infection results in depletion of total RNA in the nucleus of monoblasts and monocytes. The level of nuclear acidic proteins in monoblasts is also less, than in control during all time of infection, whereas in monocytes it is higher, than in uninfected cells at the final stage of infection. These data can be used in further researches to elucidate cytopathogenesis of ASFV infection.
Keywords: cytophotometry; infected cell; ASFV; cytopathogenesis; disease; nucleus; nucleolus